Evaluation of sediment production and siltation in a small earth dam in Fernandópolis, SP - Vanzela, Luiz S.; Grecco, Diego L. G.; Costa Neto, José N. da; Santos, Gilmar Oliveira [UNESP] (Associação Brasileira de Engenharia Agrícola, 2014)
The siltation is a natural process, but can be accelerated by human actions and results in major problems for the reservoirs, reducing its useful volume for irrigation. An example of this problem was the reduction of the area of mirror water of Fernandópolis municipal dam in 48.3% during 20 years. Therefore, this study aimed to evaluate the production of sediments and siltation of Fernandópolis municipal dam from a methodology that can be applied to small earth dams for agricultural purposes. For this, it was monitored, monthly throughout the year, the volume of sediment deposited in the reservoir. The percentage of retention sediment in Fernandópolis municipal dam ranged from 53.9 to 94.5%, that associated with a high specific sediment yield, will cause its full silting in at most 57 years. It is recommended to minimize this process the restoration of permanent preservation areas and the removal of 17,500 m³ of sediment from the riverbed of the dam.

O assoreamento é um processo natural, mas que pode ser potencializado pelas ações antrópicas e resulta em grandes problemas para os reservatórios, reduzindo seu volume útil para a irrigação. Um exemplo deste problema foi a redução da área do espelho d'água da represa municipal de Fernandópolis em 48,3%, durante 20 anos. Por isso, este trabalho teve como objetivo avaliar a produção de sedimentos e o assoreamento da represa municipal de Fernandópolis a partir de metodologia que pode ser aplicável a pequenas barragens de terra para fins agrícolas. Para isto, foi monitorado, mensalmente, durante um ano, o volume de sedimento depositado na represa. O percentual de retenção de sedimentos na represa municipal de Fernandópolis variou de 53,9 a 94,5%, que associada a uma alta produção específica de sedimentos, provocará seu completo assoreamento em, no máximo, 57 anos. Recomendam-se para minimizar este processo, a restauração das áreas de preservação permanente e a retirada de 17.500 m³ de sedimentos do leito da represa.
Avaliação da produção de sedimentos e do assoreamento em pequena barragem de terra de Fernandópolis-SP
Keywords: Hidrossedimentologia; Uso e ocupação do solo; Erosão; Hydro-sedimentology; Use and land occupation; Erosion